The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1113/jphysiol.1987.sp016684
|View full text |Cite
|
Sign up to set email alerts
|

Independent control of channel closure and block of open channels by methylxanthines at acetylcholine receptors in frog.

Abstract: 4. Caffeine or theophylline derivatives (041-4 mM), during exposure to drug, produced effects similar to those observed after the application of IBMX; namely a prolongation of the time course of e.p.c.s and m.e.p.c.s without changing the singleexponential nature of the function.5. Computer simulations were made of the m.e.p.c.s in IBMX. The effects of IBMX could be fitted to the sequential model of channel block only if the prolonged time constant observed upon wash-out was used for the rate constant of channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…Specifically, a balance between phosphorylation near the membrane and phosphorylation of more distal sites appears to determine whether a cyclic AMP analogue will produce excitation or inhibition. Based upon these results and previous results with PDE inhibitors (Silinsky, 1984;Silinsky & Vogel, 1987;Dryden et al, 1988), it is likely that the more distal of these mechanisms, i.e. the one responsible for the excitatory effects of cyclic AMP, possesses the greatest capacity to influence the secretory process.…”
Section: Discussion Cyclic Amp and Compartmentationsupporting
confidence: 62%
“…Specifically, a balance between phosphorylation near the membrane and phosphorylation of more distal sites appears to determine whether a cyclic AMP analogue will produce excitation or inhibition. Based upon these results and previous results with PDE inhibitors (Silinsky, 1984;Silinsky & Vogel, 1987;Dryden et al, 1988), it is likely that the more distal of these mechanisms, i.e. the one responsible for the excitatory effects of cyclic AMP, possesses the greatest capacity to influence the secretory process.…”
Section: Discussion Cyclic Amp and Compartmentationsupporting
confidence: 62%
“…In the present work IBMX increased the amplitude of e.p.ps, an effect that might be related to its ability to antagonize endogenous adenosine which tonically inhibits transmission at the rat diaphragm neuromuscular junction. In contrast, at the frog sartorius neuromuscular junction, IBMX does not antagonize the adenosine receptor (Ribeiro & Sebastiao, 1985) and in submillimolar concentrations has postsynaptic inhibitory effects on transmission (Ribeiro & Sebastiao, 1987), that are probably related to its ability to block the opening of acetylcholine receptors and to increase the rate constant of receptor closure (Silinsky & Vogel, 1987). Whether the apparently different behaviour of IBMX against the adenosine receptors at the rat diaphragm and frog sartorius neuromuscular junctions reflects different sensitivities of both species to IBMX itself, rather than differences in the adenosine receptor cannot be answered in the present investigation.…”
Section: Discussionmentioning
confidence: 87%
“…However, application of the phosphodiesterase inhibitor Ro20-1724 to the frog NMJ enhanced mepp frequency, an action similar to that of theophylline. Silinsky (1984) and Silinsky and Vogel (1987) have also reported that Ro20-1724 and other phosphodiesterase inhibitors increase mepp frequency. Thus, theophylline, at 100 PM and 1 mM, may increase spontaneous transmitter release in part by phosphodiesterase inhibition and enhancement of intraterminal cyclic AMP levels.…”
Section: Stimulatory Effects Of Theophyllinementioning
confidence: 96%
“…7). Silinsky (1984) and Silinsky and Vogel (1987) have also reported that Ro20-1724 increases mepp frequency and reduces the size of the endplate current.…”
Section: Effects Of Adenosine Deaminasementioning
confidence: 96%